2000
DOI: 10.1080/096452900110300
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Alumni Generosity? Evidence for the UK

Abstract: This paper examines the scale and determinants of alumni giving, using datasets from two public-sector, doctoral-granting universities in the UK. The importance of alumni generosity-both as revenue and as a performance measure-is considered, comparing new UK evidence with extant findings on US donor behaviour. Evidence is presented on systematic differences in alumni generosity, based on personal characteristics, solicitation efficiency, and the characteristics and quality of the Higher Education received by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 24 publications
8
80
1
Order By: Relevance
“…With the increasing competitiveness in the market, combined with rising educational costs and reductions in student fi nancial aid, college and university alumni are ever more essential in providing fi nancial support to their institutions ( Briechle, 2003 ;Liu, 2006 ;Weerts and Ronca, 2007 ). Research on giving to higher education generally has focused on predicting the factors and characteristics of alumni who give (e.g., Taylor and Martin, 1995 ;Baade and Sundberg, 1996 ;Okunade and Berl, 1997 ;Belfi eld and Beney, 2000 ;Clotfelter, 2003 ;Weerts and Ronca, 2007 ), the institutional and macroeconomic factors in explaining variations in giving (e.g., Briechle, 2003 ;Gunsalus, 2004 ;Liu, 2006 ), alumni motivation for giving (e.g., Diamond and Kashyap, 1997 ;Weerts and Ronca, 2007 ), fundraising practices in higher education (e.g., Harrison, 1995 ;Harrison et al , 1995 ), and the determinants of donor revenue (e.g., Cunningham and Cochi-Ficano, 2001 ; see review of literature in Liu, 2006 ).…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing competitiveness in the market, combined with rising educational costs and reductions in student fi nancial aid, college and university alumni are ever more essential in providing fi nancial support to their institutions ( Briechle, 2003 ;Liu, 2006 ;Weerts and Ronca, 2007 ). Research on giving to higher education generally has focused on predicting the factors and characteristics of alumni who give (e.g., Taylor and Martin, 1995 ;Baade and Sundberg, 1996 ;Okunade and Berl, 1997 ;Belfi eld and Beney, 2000 ;Clotfelter, 2003 ;Weerts and Ronca, 2007 ), the institutional and macroeconomic factors in explaining variations in giving (e.g., Briechle, 2003 ;Gunsalus, 2004 ;Liu, 2006 ), alumni motivation for giving (e.g., Diamond and Kashyap, 1997 ;Weerts and Ronca, 2007 ), fundraising practices in higher education (e.g., Harrison, 1995 ;Harrison et al , 1995 ), and the determinants of donor revenue (e.g., Cunningham and Cochi-Ficano, 2001 ; see review of literature in Liu, 2006 ).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The extant research has looked at the individual characteristics of donors as well as those in households -examining how gender, education, income, age, race, and marital status affect charitable giving behavior (e.g., Belfi eld and Beney, 2000 ;Conley, 2000 ;Andreoni et al ., 2003 ;Bryant et al ., 2003 ;Rooney et al , 2005 ;Mesch et al ., 2006 ). Very little research exists, however, as to the charitable giving decision-making process itself. "…”
Section: Who Decides In Giving To Education? a Study Of Charitable Gimentioning
confidence: 99%
“…As age increases and families mature, so does capacity and the likelihood of increased philanthropic contributions to their alma mater ( Pendel, 1985 ;Connolly and Blanchette, 1986 ;Hueston, 1992 ). Many studies suggest that giving is associated with occupation, increases in age and household income ( Olsen et al ., 1989 ;Baade and Sundberg, 1996 ;Belfi eld and Beney, 2000 ;Wunnava and Lauze, 2001 ;Clotfelter, 2003 ;Monks, 2003 ;Thomas and Smart, 2005 ).…”
Section: Capacity To Give and Volunteermentioning
confidence: 99%
“…Several researchers (Belfield & Beney, 2000;Clotfelter, 2003b;Hanson, 2000;Mael & Ashforth, 1992;Monks, 2003) have found undergraduate experience to have a significant impact upon alumni giving behavior, with Monks reporting that satisfaction with one's undergraduate experience is the single biggest determinant of alumni giving. Bruggink and Siddiqui (1995) revealed that "fond memories" of the institution, which were likely a result of a positive undergraduate experience, resulted in a positive relationship with alumni giving.…”
Section: Student Experiencesmentioning
confidence: 99%
“…The perception of alumni of the academic quality and prestige of their alma mater is another factor of alumni giving found in research, with greater perceived quality and prestige leading to greater levels of alumni giving (Belfield & Beney, 2000;Clotfelter, 2003b;Hanson, 2000;Leslie & Ramey, 1988;Mael & Ashforth, 1992). In a study of alumni of a liberal arts institution, however, Holmes (2008) found that an increase in academic prestige actually had a negative impact on giving, reporting that when the institution studied falls one place in the US News and World Report rankings it realizes a 46 2% increase in giving.…”
Section: Institutional Characteristicsmentioning
confidence: 99%